2017
DOI: 10.1186/s12909-017-1093-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a novel population panel management curriculum among interprofessional health care trainees

Abstract: BackgroundGaps in chronic disease management have led to calls for novel methods of interprofessional, team-based care. Population panel management (PPM), the process of continuous quality improvement across groups of patients, is rarely included in health professions training for physicians, nurses, or pharmacists. The feasibility and acceptance of such training across different healthcare professions is unknown. We developed and implemented a novel, interprofessional PPM curriculum targeted to diverse health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Few studies have looked at panel management curricula in residency. [11][12][13][14]18 Most focused on clinical outcomes based on health metrics and processes of care measures, such as completion of laboratory tests, vaccinations, or visits. [11][12][13][14] In our study, residents reported increased processes of care, which is concurrent with previous work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have looked at panel management curricula in residency. [11][12][13][14]18 Most focused on clinical outcomes based on health metrics and processes of care measures, such as completion of laboratory tests, vaccinations, or visits. [11][12][13][14] In our study, residents reported increased processes of care, which is concurrent with previous work.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed learner outcomes, consisting of self-reported improvements in panel management skills, confidence in chronic care delivery, self-management goal-setting, and/or sustained behavior change, but most studies did not elaborate about what residents felt was successful about the curricula. 13,14,18 Our thematic analysis of residents' reflections on successes and barriers can inform further work by identifying particularly strong elements of a panel management curriculum as well as elements that may need improvement. In our case, the teamwork element of the curriculum and the positive effect on resident-patient relationships were key strengths identified by residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TIP Program provides a model to address the current lack of established methods for trainees to learn interprofessional collaboration across the primary-secondary-tertiary care divide. 22,[39][40][41][42][43] Consequently, the TIP Program can provide opportunities for trainees to move beyond the traditional consultant model and actively participate in interprofessional teamwork. Furthermore, the specialist physicians participating in the TIP Program provide a role model for successful interprofessional collaborations and, as such, provide learners exposure to a real-world model for caring for people with multimorbidity in the primary care context.…”
Section: Openmentioning
confidence: 99%
“…Of the 27 selected reports, 18 studies measured perceived confidence in or comfort with performing certain tasks. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Six studies measured competency or ability, 10,13,[22][23][24][25] two studies measured readiness, 9,16 and five studies e92 lacked sufficient detail to determine what they used. [26][27][28][29][30] Measuring one's willingness to perform a task or one's confidence helps promote reflection of performance 3 but is not the most effective method of evaluating learning or performance.…”
Section: E91mentioning
confidence: 99%